Digital Maturity Models: A Holistic Framework for Digital Transformation - YILMAZ, KEMAL ÖZKAN (IGI Global, 2023)
This chapter aims to create a general framework on digital maturity models and reveal the highlights of the commonly used components of digital maturity models. The emphasis will be more on detailing human-related fundamental aspects of digital maturity models rather than the technological ones. Considering the incrementally increasing options to reach collaboration technologies and swift deployment of them to different sectors, the main challenge still remains as to manage the psychological asset related parts. Although technology is generally perceived as mechanical, whose boundaries can be drawn, tasks to be assigned can be defined; the technological elements within the concept of digital maturity also intersects with the human-related dimensions of digital transformation. The study aims to advise a systematic approach by offering a theoretical framework to manage human-related factors in a digital transformation journey with an inclusive perspective positioning technology as the core medium provider and contributes to the theoretical background in the field of study.
▪️ Source Title: Handbook of Research on Digitalization Solutions for Social and Economic Needs.